Phosphoglucose Isomerase Plays a Key Role in Sugar Homeostasis, Stress Response, and Pathogenicity in Aspergillus flavus - Zhou, Yao; Du, Chao; Odiba, Arome Solomon; He, Rui; Ahamefule, Chukwuemeka Samson; Wang, Bin; Jin, Cheng; Fang, Wenxia (Frontiers in Cellular and Infection Microbiology, 2021)
Aspergillus flavus is one of the important human and plant pathogens causing not only invasive aspergillosis in immunocompromised patients but also crops contamination resulting from carcinogenic aflatoxins (AFs). Investigation of the targeting factors that are involved in pathogenicity is of unmet need to dismiss the hazard. Phosphoglucose isomerase (PGI) catalyzes the reversible conversion between glucose-6-phosphate and fructose-6-phosphate, thus acts as a key node for glycolysis, pentose phosphate pathway and cell wall biosynthesis in fungi. In this study, we constructed A. flavus pgi deletion mutant, which exhibited specific carbon requirement for survival, reduced conidiation and slow germination even under the optimal experimental conditions. The Δpgi mutant lost the ability to form sclerotium and displayed hypersusceptibility to osmotic, oxidative and temperature stresses. Furthermore, significant attenuated virulence of the Δpgi mutant was documented in Caenorhabditis elegans infection model, Galleria mellonella larvae model and crop seeds. Our results indicate that PGI in A. flavus is a key enzyme in maintaining sugar homeostasis, stress response and pathogenicity of A. flavus. Therefore, PGI is a potential target for controlling infection and AFs contamination caused by A. flavus.